1987
DOI: 10.1021/jm00393a040
|View full text |Cite
|
Sign up to set email alerts
|

Streptonigrin and lavendamycin partial structures. Probes for the minimum, potent pharmacophore of streptonigrin, lavendamycin, and synthetic quinoline-5,8-diones

Abstract: The preparation and evaluation of 7-amino-5,8-dioxo-2-(2'-pyridyl)quinoline-6'-carboxylic acid (5a) and 7-amino-2-(2'-aminophenyl)-5,8-dioxoquinoline-5'-carboxylic acid (6a) constituting potential minimum, potent pharmacophores of streptonigrin (1a) and lavendamycin (2a), two structurally related naturally occurring antitumor antibiotics, are detailed. In contrast to observations associated with streptonigrin and lavendamycin in which the C-ring C-6' carboxylic acid potentiates the antitumor, antimicrobial, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
53
0
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(54 citation statements)
references
References 5 publications
0
53
0
1
Order By: Relevance
“…The 5,8-quinolinedione derivatives were among the first compounds to be systematically modified in order to find products with higher biological activities, such as anticancer, anti-inflammatory or antibacterial [1][2][3][4][5][6][7][8][9]. For example, it was found that substitution of the electron-withdrawing groups at the 6-or 7-positions of the 5,8-quinolinedione led to an increase in the DNA degradation [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The 5,8-quinolinedione derivatives were among the first compounds to be systematically modified in order to find products with higher biological activities, such as anticancer, anti-inflammatory or antibacterial [1][2][3][4][5][6][7][8][9]. For example, it was found that substitution of the electron-withdrawing groups at the 6-or 7-positions of the 5,8-quinolinedione led to an increase in the DNA degradation [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Метиленовый синий (известный ингибитор NO-зависимой активации растворимой гуанилатциклазы) также тормозит рост лейкемических клеток L 1210 и Р388. Ранее было показано, что противоопухолевый антибиотик стрептонигрин (брунеомицин) тормозит рост лейкемических клеток L1210 [56,57]. Биохимический механизм фармакологического действия стрептонигрина исследовался детально только с точки зрения его влияния на нуклеиновые кислоты.…”
Section: роль растворимой гуанилатциклазы в действии стрептонигрина (unclassified
“…Derivatives of quinoline-2-carboxylic (quinaldic) acid [1] are used as model structures of natural antibiotics [2] and biologically active protein molecules [3] and appear in the composition of triostin [4] and saframycin A [5]. The quinaldic acid structural unit is found in Ephedra sp.…”
mentioning
confidence: 99%